The importance of sleepers spacing in railways - Ortega, Roberto Sañudo (2021)
The railway tracks are composed of steel rails that are supported by the infrastructure through sleepers, which are generally assembled with a fixed separation between them. Sleepers and fastenings are the most numerous elements of the superstructure. The global cost of these elements is directly proportional to their number along the track. Therefore, the reduction of the number of these components can generate relevant reductions of track construction costs. Nonetheless, very few studies focused on the optimal sleeper spacing and its consequences. Moreover, the railway industry uses fixed separation values based on past experience, rather than on scientific knowledge. In line with this reasoning, the objective of this work is to analyse the optimal sleeper spacing in order to contribute to the minimization of track costs. The work starts from an overview of the sleepers spacing used over the world and analyses how this can affect the track performance. This study is valuable for design and construction of new tracks, as well as for the maintenance and renewal of existing ones, helping to achieve cost savings for the rail industry, positive environmental results and consequent contributions to the competitiveness of rail transport.